2008
DOI: 10.1038/ijo.2008.244
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery and reduction in morbidity and mortality: experiences from the SOS study

Abstract: Obesity is associated with increased morbidity and mortality. Intentional weight loss results in improvement of cardiovascular risk factors, but most observational studies suggest that weight reduction is associated with increased overall and cardiovascular mortality. No prospective intervention studies on mortality have earlier been reported in obese subjects. The prospective, controlled Swedish Obese Subjects Study enrolled obese subjects who either underwent bariatric surgery (n ¼ 2010) or were allocated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
161
0
21

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(185 citation statements)
references
References 24 publications
3
161
0
21
Order By: Relevance
“…Weight loss evolves rapidly, and currently bariatric surgery has increasingly become recognized as a highly effective alternative for achieving major weight reduction for obese patients. A large prospective cohort study [Swedish Obese Subjects (SOS) study] found that weight loss was still apparent 10 years following surgery, whereas patients receiving conventional treatment had gained weight (22).…”
Section: Osteoporosis and Obesity Treatmentsmentioning
confidence: 99%
“…Weight loss evolves rapidly, and currently bariatric surgery has increasingly become recognized as a highly effective alternative for achieving major weight reduction for obese patients. A large prospective cohort study [Swedish Obese Subjects (SOS) study] found that weight loss was still apparent 10 years following surgery, whereas patients receiving conventional treatment had gained weight (22).…”
Section: Osteoporosis and Obesity Treatmentsmentioning
confidence: 99%
“…1 Weight loss regimens, including pharmacological treatments, are most often not efficacious in the long run, whereas gastric bypass (GBP) surgery is associated with a pronounced weight loss that is maintained over long time periods. 2 During the last two decades, much attention has been paid to the function of the endothelium, 3 in particular as endothelial dysfunction has been shown to predict cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…The large Swedish obese subjects study reported mortality of 0.25% in the surgical cohort (5/2010 patients within 90 days of surgery) (2). Major adverse events following surgery include anastomotic leakage, pneumonia, pulmonary embolism, band slippage and band erosion (5).…”
Section: Discussionmentioning
confidence: 99%
“…Seven randomized controlled trials (RCTs) have reported an average reduction of 20% to 32% in initial body weight (depending on surgery technique) after 1-2 years of surgery (1). The Swedish Obese Subjects study (2) clearly showed that weight loss following surgery sustained 10 years post-surgery, whereas non-surgical treatment modalities did not result in long-term weight loss. Despite high percentages of weight loss, bariatric surgeries have been shown to result in many adverse events including neuropathies (3,4).…”
Section: Introductionmentioning
confidence: 99%